The effects of ad libitum fluid ingestion on fluid balance during alpine skiing in recreational skiers - Seifert, J. G.; Burke, E. R.; White, A.; Luetkemeier, M. J. (Journal of Sports Sciences, 2006)
The aim of this study was to assess the influence of ad libitum water ingestion, using a back-mounted hydration system (BMHS), on fluid balance during alpine skiing. Fourteen skiers skied on two different days. On one day, seven skiers ingested water during skiing via the BMHS and the other seven skiers refrained from fluid ingestion during skiing until the midday break (NW trial). On the second day, the trials were reversed. Results indicated that when skiers used the BMHS they drank significantly more water than during the NW trials (2.0 ± 0.9 vs. 0.78 ± 0.4 litres). However, skiers drank significantly more at the midday break during the NW trials than during the BMHS trials (0.78 ± 0.4 vs. 0.4 ± 0.2 litres). Percent change in plasma volume was less during the BMHS trials than during the NW trials (-0.1 ± 5.3 vs. -4.9 ± 5.2%), urine osmolality was maintained in the BMHS trials but rose from 295 ± 80 to 818 ± 168 mOsm · kg-1 at midday during the NW trials, and body mass loss was minimized during the BMHS trials compared with the NW trials (0.4 ± 0.4 vs. 1.1 ± 0.2 kg). Skiers reported that they felt significantly better when they ingested water during the BMHS trials. In conclusion, a back-mounted hydration system allowed the skiers to maintain hydration status.